2005
DOI: 10.1002/adfm.200400615
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Covalent Approach for Depositing Spatially Selective Materials on Surfaces

Abstract: We describe a new method for depositing patterned materials, based on non‐covalent trapping of ligands in solvent‐templated nanocavities created in aromatic, self‐assembled monolayer or polymer films. A model has been developed and tested to describe nanocavity formation and the ligand adsorption process, which occurs via ligand exclusion from ambient, aqueous solution into the hydrophobic nanocavities. Ligand adsorption rates and ligand adsorbate reactivity with solution species are governed by ligand size/ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 90 publications
3
62
0
Order By: Relevance
“…Reduction and immersion in an electroless metallization bath create micropatterns of metal, e.g. nickel, with sharp boundaries on top of the silane layer [180] .…”
Section: Electroless Nano-nickel On Cnt and Sam Layersmentioning
confidence: 99%
“…Reduction and immersion in an electroless metallization bath create micropatterns of metal, e.g. nickel, with sharp boundaries on top of the silane layer [180] .…”
Section: Electroless Nano-nickel On Cnt and Sam Layersmentioning
confidence: 99%
“…The BiAs-Bi/SiC junction provides a robust platform for QSVHK states, protected by a global gap of 287 meV, which is ∼ 14 times larger than in BLG [20], supporting ballistic transport at high temperatures. Even multiple QSH-QVH boundaries can be flexibly created by spatially-selective deposition [62,63], i.e., by alternating depositing Bi and BiAs arrays on SiC substrate, enabling transport of high-density channels. Unlike in BLG, the QSVHK states in bismuthene-based system are spin polarized and require no external field.…”
mentioning
confidence: 99%
“…Experimental parameters such as the environmental conditions and solvent choice affect the density of organosilane thin films [ 37 38 ]. A model was proposed for the self-assembly of CMPS nanostructures formed within areas of nanoholes which subsequently grew to form multiple layers of CMPS through self-polymerization [ 37 , 39 ]. In a recent report, we have shown that changes in the parameters of temperature and solvent affect the growth of CMPS nanostructures prepared within a matrix film of organosilanes prepared with particle lithography [ 40 ].…”
Section: Introductionmentioning
confidence: 99%